An innovative microcoring technology: A novel approach to acne scar treatment - Ahn, Hyo‐Sang; Kim, Soo‐Kyung; Pamela, Ruri; Lu, Pei‐Hsuan; Vachatimanont, Vanravi; Putri, Ardhiah Iswanda; Tanojo, Henry; Yi, Kyu‐Ho (Skin research and technology, 2024)
Background Acne scars present a complex challenge in dermatology and cosmetics, despite advancements in technological interventions such as fractional lasers, microneedling, and surgical procedures. Effective treatment remains elusive for many individuals. Objective This study aims to evaluate the efficacy of rotational fractional resection using 1 mm diameter rotating scalpels as a primary treatment for icepick and boxcar scars on the cheeks and glabella region. Methods Three patients with acne scars underwent a single treatment session of rotational fractional resection. Evaluation occurred at the 2‐month post‐treatment mark to assess improvements in scar appearance and potential skin‐related side effects. Results Following the treatment, significant improvements were observed in the targeted acne scars. Notable enhancements were noted without major skin‐related adverse effects, except for minor suture marks. Conclusion The outcomes of this study underscore the potential of rotational fractional resection as an innovative and effective approach in treating acne scars. This single‐session cosmetic procedure shows promise in yielding lasting and quantifiable results, offering a hopeful solution for individuals seeking comprehensive acne scar treatment.